Marine pollution : sources, fate and effects of pollutants in coastal ecosystems - Beiras, Ricardo (Elsevier, 2018)
Marine Pollution: Sources, Fate and Effects of Pollutants in Coastal Ecosystems bring together the theoretical background on common and emerging marine pollutants and their effects on organisms (ecotoxicology). Written by a well-renowned expert in the field who is a researcher, teacher and advisor of national and international institutions on issues, such as oil spills, water quality assessment and plastic pollution, the book offers a thorough account of the effects (ecotoxicology) of pollutants on marine organisms and the public health implications, along with the biological tools advocated by the international institutions for marine pollution monitoring. Marine Pollution: Sources, Fate and Effects of Pollutants in Coastal EcosystemsiApresentsiAinformation in a rigorous and contrasted manner derived from a comprehensive review of solid scientific knowledge, but also illustrated with examples of practical applications.